Pendekatan House Of Risk Untuk Penilaian Risiko Alur Penyediaan Dan Pendistribusian Obat (Studi Kasus Pada Apotek ABC) - Guntur Samodro (OPSI, 2020)
Pharmacy "ABC" is a trading business in Gunungkidul Regency, D.I. Yogyakarta which is engaged in the pharmaceutical and medical devices. In order to improve the performance of Pharmacy "ABC" in serving and meeting customer needs, it is necessary to identify risks and also mitigate so that supply chain risk management can run according to its function. As for the risk assessment in this study using the House of Risk (HOR). From the research which was conducted at Pharmacy "ABC", there were 17 risk events and 13 risk agents. Based on House of Risk 2 calculations, a risk management strategy will be obtained that is easy to do and can help mitigate the supply chain risk management (SCRM) process at Pharmacy "ABC". Risk management strategies that can be implemented in Pharmacy "ABC" are sharing and updating information with Distributors, building an intensive communication system via Whatsapp, making agreements with distributors regarding the timing of drug delivery to pharmacies, forecasting demand based on historical data and finally sharing and medical education to customers.